Disasters and earthquake preparedness of children and schools in Istanbul, Turkey - Ersoy, Sukru; Kocak, Ali (TAYLOR & FRANCIS LTD, 2016)
Unless decision makers urgently exhibit a proactive approach to earthquake preparedness, Istanbul will be the most vulnerable city for the expected great Marmara Earthquake and Tsunami. Because Istanbul has the highest population density (larger than some European countries) and is the commercial/industrial centre of Turkey, the high seismic potential of the North Anatolian Fault (NAF) in the Sea of Marmara is a great risk for Istanbul.The Kocaeli and the Duzce earthquakes, which were the last two seismic events to occur in the eastern part of Marmara in 1999, dramatically demonstrated the vulnerability and lack of awareness and preparedness of Istanbul and the Marmara region for natural disasters. Although Istanbul is 90 km from the epicentre of the earthquake that occurred in 1999, it caused severe damage to many buildings and great loss of life. An earthquake of even greater magnitude is now expected to occur within the submarine fault system that extends west of the 1999 ruptured segments under the Sea of Marmara which is near Istanbul.Although Istanbul is susceptible to seismic hazards and a destructive earthquake and tsunami are anticipated to occur in the Marmara Sea, necessary seismic risk mitigations have not been taken. Disaster preparedness studies, which are conducted by the government and the municipality of Istanbul, are not sufficient or rapid enough. School students, especially, in their unsafe school buildings, are the most vulnerable to earthquakes. The disaster-related issues are so serious because of the students >23 million in Turkey or approximate to 4 million students in Istanbul, and frequently repeated disaster events.
Keywords: NORTH ANATOLIAN FAULT; MARMARA SEA REGION; SEISMICITY; TSUNAMIS; Geology; Meteorology & Atmospheric Sciences; Remote Sensing; Water Resources